Increasing system test coverage in production automation systems. (April 2018) - Ulewicz, Sebastian; Vogel-Heuser, Birgit
Abstract: An approach is introduced, which supports a testing technician in the identification of possibly untested behavior of control software of fully integrated automated production systems (aPS). Based on an approach for guided semi-automatic system testing, execution traces are recorded during testing, allowing for a subsequent coverage assessment. As the behavior of an aPS is highly dependent on the software, omitted system behavior can be identified and assessed for criticality. Through close cooperation with industry, this approach represents the first coverage assessment approach for system testing in production automation to be applied on real industrial objects and evaluated by industrial experts. Highlights: Approach for system test coverage assessment in automated production systems. Untested system behavior is identified using execution tracing. The approach is independent from simulations or formalized requirements. An industrial machine was used for an evaluation with industrial experts.